Community Structure of Gastropods in the Mangrove Ecosystem in the Mengkapan Village, Sungai Apit District, Siak Regency, Riau Province - Devi Sulastri; Adriman Adriman; Muhammad Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractOn the coast of Mengkapan Village there is a mangrove forest covering an area of ± 30 Ha. The condition of mangrove forest has been changed due to domestic waste and oil spills.Secondary impact of mangrove ecosystem changes affect the associated organisms such as gastropods. To understand the community structure of gastropods in that mangrove ecosystem, a research was conducted on February-March 2018. The methods used in this research is survey method. There were 3 line transects and in each line there were 3 plots (1mx1m). The gastropods present in the plots were collected manually every two weeks. Results shown that there were 9 gastropods species present, they were Cassidula aurisfelis, Cerithidea obtusa, Cerithidea quadrata, Cerithideopsilla alata, Chicoreus capucinus, Indothais gradata, Littoraria melanostoma, Nerita lineata dan Telescopium telescopium. The gastropods abundance was ranged from 15-26 organisms/m2. The value of diversity index was (H') 2.46-2.81, the dominance index (C) was 0.17-0.24 and the uniformity index (E’) was 0.82-0.89. The water quality parameters are as follows: temperature was 25-28 0C, pH of the water was 7-6, pH of the soil was 6-7 and salinity was 22-260/00. Data obtained from this research indicate that the anthropogenic activities in the Mengkapan Village slightly affects the gastropod community. Keywords:Diversity Index, Dominance Index, Coastal Area,Line Transect, Anthropogenic